Infection and preterm birth. Issue 2 (April 2016) - Nadeau, Hugh C.G.; Subramaniam, Akila; Andrews, William W.
Summary: Preterm birth (PTB) remains a primary cause of neonatal morbidity and mortality. The purpose of this article is to outline the association between infection and PTB. We performed a search of the PubMed database for relevant scientific work published in English from 1995 to July 2015. Whereas there is substantial evidence regarding infection as a strong risk factor for preterm birth, the role of specific bacterial and viral infections is not totally conclusive. Newer high-dimensional biological technologies such as microbiomics and metabolomics offer hope to identify the causative pathogens. In addition, strategies have been developed to reduce PTB.